Construction of a daily precipitation grid for southeastern South America for the period 1961–2000. (1st November 2012) - Jones, P. D.; Lister, D. H.; Harpham, C.; Rusticucci, M.; Penalba, O.
ABSTRACT: Daily station precipitation totals are used to develop a gridded dataset for the region (14°–40°S, 45°–70°W) on a 0.5° × 0.5° latitude/longitude grid, primarily for comparison with regional climate model (RCM) simulations. The gridded dataset covers the period 1961–2000. Much of the paper discusses the quality control of the basic station precipitation series. Although the primary aim of the development has been RCM validation, we have assessed trends in seasonal precipitation totals as well as trends in two measures of precipitation extremes (R95p, the daily precipitation amount exceeded only 5% of the time and Rx5day, the maximum 5‐d precipitation total during each season). Relatively few regions across the large domain have statistically significant trends, but those that do tend to be located in the eastern two thirds of the grid, particularly over southeastern Brazil and Uruguay. Significant trends are also more evident in the DJF and MAM seasons. There is good spatial agreement between the trends in seasonal totals and trends in the extreme indices.